Perancangan Drilling Jig dengan Adjustable V-Block untuk Pengeboran Tangkai Drill Chuck Mesin Bor Koordinat 22 STA - Ilham Akmal; Hamdi Hamdi; Darius Yuhas (Jurnal Mekanik Terapan, 2022)
The drill machining process requires the drill chuck shank as a coupler between the drill chuck and the drilling machine spindle. Limited availability of drill chuck shank especially for coordinate drilling machine 22 STA is the problem faced. The purpose of the design is to get a replacement of drill chuck shank because on the market that thing is difficult to obtain. The design methods include: the design of special device for placing the drill chuck shank in parallel position to the horizontal axis that is drilling jig with adjustable v-block to adjust the taper of the shank,machining a drilling jig with adjustable v-block, and trial drilling of eight holes on body of drill chuck shank. The real result obtained is drilling jig with adjustable v-block which can be used to make eight holes on body of drill chuck shank coordinate drilling machine 22 STA.